Peranan Cerita Rakyat Nusantara dalam Meningkatkan Literasi Budaya dan Kewargaan Siswa - Oktafianti, Monica; Dewi, Dinnie Anggraeni; Hayat, Rizky Saeful (Indo-MathEdu Intellectuals Journal, 2024)
Cultural literacy skills are important to have so that students are not easily influenced by foreign cultures that enter. By improving their cultural literacy skills, they will better appreciate, maintain, and preserve the local culture found in the Indonesian community. The aim of writing this article is to see the role of Indonesian folklore in increasing student literacy, especially elementary school students. The research method used is a qualitative method with a library study approach. Data obtained by searching for journals, e-books and articles related to keywords and discussion topics. The results of the research show that folklore can improve students' literacy skills, especially by increasing character values ​​and knowledge of the unique characteristics of each region in Indonesia